Effect of fuzzy logic controller on voltage stability of parallel boost converter configuration - Kusmantoro, Adhi; Hiyama, Takashi (SHM Publisher, 2023)
An increase in electricity load causes a change in grid voltage and current, causing losses to customers. In addition, the source of electricity from fossil energy has also decreased. Therefore this study aims to provide a stable DC voltage source from solar panels, with a Fuzzy Logic Controller (FLC). The proposed method is to design a boost converter in parallel with its output. The boost converter is used to increase the DC voltage from 24 V to 48 V. In this study, FLC is used to adjust the output voltage of each boost converter. This is so that if one of the boost converters fluctuates, the other boost converters will supply a voltage according to the load voltage. The results showed that the FLC can adjust the boost converter output voltage changes. Whereas when using the PI (Integral Proportional) controller, a voltage spike occurs in the range of 0 seconds to 0.6 seconds and the voltage stabilizes within 0.6 seconds to 1 second.